Associations Between Geodemographic Factors and Access to Public Health Services Among Chinese Floating Population - Guan, Ming (Frontiers in Public Health, 2020)
Background: The floating population in urban China is facing multiple barriers to access to comprehensive, affordable, and culturally effective public health services. However, little is known about the role of geodemographic factors. This study aimed to assess the associations between geodemographic factors and access to public health services among the Chinese floating population. Methods: This study employed the data from the 2015 Migrant Dynamic Monitoring Survey data in China. Descriptive statistical analysis and principal component analysis were used to provide basic characteristics of the main variables. Multiple logistic models were used to analyze how province-level units, economic regions, and economic zones had significant associations with residential health records establishment, social medical insurance, and types and methods of health knowledge attainment in urban China. Using multiple indicator multiple cause models, the association between geodemographic factors and types and methods of health knowledge attainment was studied. Results: The results indicated that there was regional unbalance in the case of residential health records. Regional differences were significantly associated with social medical insurance. Provincial differences were significantly associated with health knowledge attainment. There were regional differences in the methods of health knowledge attainment. In the most provincial units, geodemographic factors had significant associations with types and methods of health knowledge attainment. Conclusions: This study confirmed empirical associations between geodemographic factors and access to public health services among Chinese floating population. The relevant suggestion was that provincial units with less-developed public health services should enhance their capabilities to equalize public health services.